Self-Efficacy and Emotion Regulation as Predictors of Teacher Burnout Among English as a Foreign Language Teachers: A Structural Equation Modeling Approach - Bing, Hang; Sadjadi, Bakhtiar; Afzali, Maryam; Fathi, Jalil (Frontiers in Psychology, 2022)
Since teachers and their psychological factors have a significant share of variance in accounting for success in educational contexts, significant number of empirical studies have investigated the associations among intrapsychic variables of teachers. To further examine the inter-connections between individual teacher constructs in English as a Foreign Language (EFL) contexts, this study explored the role of emotion regulation and teacher self-efficacy in predicting teacher burnout in the Chinese EFL context. In so doing, a sample of 174 EFL teachers completed a survey containing the three valid scales measuring these constructs. Structural Equation Modeling was employed to examine the structural model of the variables under investigation. The findings revealed that teacher self-efficacy accounted for 20 % of the variance in burnout whereas emotion regulation represented 11.2% of the teacher burnout variance. Overall, it was revealed that although both variables exerted a significant unique contribution to teacher burnout, teacher self-efficacy seemed to be a stronger predictor of burnout than emotion regulation of teachers. The results might have remarkable implications for EFL teacher development programs.